A Comparative Study of Characteristics and Outcomes of Patients with Proved and Suggested Sarcoid Uveitis Occurring after Ophthalmic Procedure. (18th October 2018) - Jamilloux, Yvan; Taleb, Aude; De Parisot, Audrey; Pérard, Laurent; Burillon, Carole; Broussolle, Christiane; Kodjikian, Laurent; Sève, Pascal
Abstract : Purpose . To describe patients with new onset sarcoid uveitis occurring after an ophthalmic procedure and compare them with patients with sarcoid uveitis without ocular procedure. Methods . Retrospective analysis of case records from patients with postophthalmic procedure sarcoid uveitis seen at our institution between April 2004 and October 2016. Patients with a previous history of uveitis were not included. Each patient was randomly matched with four controls from our incident cohort of new onset sarcoid uveitis without ophthalmic procedure. Results . We identified 11 patients (8.5%) from our incident cohort of sarcoid uveitis (n = 130 ), who were all women, with a postophthalmic procedure uveitis (mostly after cataract surgery (36%)). These patients were older (69.7 vs 52.7 years) and presented more synechiae than controls. After a mean follow-up of 30 (3–60) months, there was no significant difference between the postprocedure and the control group with regard to demography, clinical presentation, disease course, treatment, and outcome. Conclusions . Sarcoid uveitis has similar characteristics in patients with new onset sarcoid uveitis after or without ophthalmic procedure. As a consequence, ophthalmic intervention should be seen as a potential trigger of latent sarcoidosis.